(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
This article analyzes the federal capital cities of Europe on the basis, first, of the policy relevance that have this type of cities, since they are the product of the historical circumstances what through States and territories, and reflect both the past and the present, in political, economic and cultural terms. Secondly, the article focuses on the European States, and the state of the Spanish autonomous regions, since although it is not a federal model, is similar in function and structure. Since in such States is complex to maintain the territorial balance, both at the political level and in the economic and cultural also, and capitals cities reflect these difficulties. We propose to analyze the european federal capital cities a classification which includes three levels, briefly describing each of them and compare them.